Increase Menopause Symptoms of Women with Hormonal Contraceptive in Surakarta - Tatik Trisnowati; Rahayu Setyaningsih (Universitas Muhammadiyah Surakarta, 2024)
During menopause, a woman will experience physical and psychological changes which often cause various complaints. There are several factors that are thought to be the cause of these complaints, such as education, use of hormonal contraceptives, and psycholog. The purpose of this study was to determine the severity of menopausal symptoms in terms of history of contraceptive use. This type of research is descriptive quantitative with cross sectional data collection using the Menopause Rating Scale questionnaire, with sampling techniques using non probability consecutive sampling techniques. inclusion criteria women aged 45 - 59 years and have stopped menstruating, have a history of using hormonal contraceptives, willing to be a respondent conducted in March 2024 until the number of respondents was obtained 30 people.  Univariate analysis test with frequency distribution. The results showed that the severity of menopausal symptoms in women using contraceptives was none 3%, mild 33%, moderate 37%, and severe 27%. Conclusion of this study is the severity of menopausal symptoms in women who use hormonal contraceptives on average have moderate severity. The severity of menopausal symptoms is not only influenced by contraceptive use, but there are other factors such as education and psychological conditions.